Characterization of SiO₂/C Composites from Bamboo Leaves and Graphite for Lithium-Ion Battery Anode - Tika Paramitha; Farhan Adisa; Muhammad Hayyi Rahman Hakim; Tifa Paramitha (Program Studi Pendidikan Kimia FKIP Universitas Sebelas Maret, 2025)
Silicon dioxide (SiO₂) is a key component found in various biomass materials, including bamboo leaves. This study aims to synthesize SiO₂/C composites using bamboo leaves as the silica source and graphite as the carbon source, targeting their application as anode materials in lithium-ion batteries (LIBs). Silica particles were first prepared using the sol-gel method and characterized by Fourier Transform Infrared Spectroscopy (FTIR), X-ray Diffraction (XRD), and Scanning Electron Microscopy (SEM). The SiO₂/C composite was synthesized through a solid-state reaction by mixing SiO₂ and graphite in varying SiO₂ weight percentages of 0%, 5%, 20%, and 100%, followed by calcination at 500 °C for 30 minutes under argon atmosphere. The morphology and composition of the resulting composites were analyzed using SEM-EDX. These composites were then employed as anode materials in LIBs, paired with a nickel manganese cobalt oxide (NMC) cathode. Electrochemical performance was assessed using a battery analyzer, and charge-discharge cycle (CDC) data were obtained. The addition of carbon significantly improved the electrochemical performance. Specifically, the composite with 100% SiO₂ showed a low capacity of 9.88 mAh/g, while those with 5% and 20% SiO₂ demonstrated significantly enhanced specific capacities of 97.35 mAh/g and 129.34 mAh/g, respectively, after five cycles.